The Influence of Social Media Marketing, Menu Variation and Price on Purchasing Decisions at Rumakadua Cafe - Mappe, Eka Satirianisa; Buamonabot, Irfandi; Zain, Zandy Pratama (AIBPM Publisher, 2024)
The purpose of this study is to ascertain how prices, menu changes, and social media marketing affect customers' decisions to buy from the Rumakadua cafe. This kind of study employs a quantitative methodology. 112 respondents made up the study's sample, and SPSS Statistics 29 software was utilized to analyze the data using multiple linear regression analysis techniques. The study's findings suggest that pricing, menu changes, and social media marketing all significantly influence the factors that influence consumers' decisions to buy